A descriptive study of the families of overseas workers in Barangays Baldoza, Ingore, Kaingin & Lopez-Jaena Sur, La Paz, Iloilo City. - Bacordo, Eugenio Felix J. (1983.)
Overseas employment has dynamically changed the lives of the concerned families in the barangay studied., On the psycho-social level, the spouse has, by the exercise of both parental authority developed independence and strenght of character. New interests were created and friendships formed. The children has been observed to be less disciplined. As they are more or less with the same peers in the same barangays, the validity of this has yet to be proven. Relatives and friends due to increased incomes of the family became dependent for financial matters and recommendations for employment overseas. Due to the structure of kinship and neighborhood in the semi-rural area, the families of overseas workers are in turn obligated. Prestige is observed in the families' activities in the affairs of the barangay, and the schools of their children. This is supported by their early memberships. On the economic level, the transformation is obvious. Incomes earned are as much as 400-477 of the previous classifying them with the top 15 of the population of Region 6, outdoing their white collar counterparts. Consumption increased to include more and better foodstuffs and their homes equipped with appliances. Prioritization of the budget shifts from subsistence to more durable permanent items such as construction of homes. Finally, their level of aspirations took middle class proportions. Tertiary education for their children became a realizable goal. It is through this education that they shall establish themselves as the new middle class of the nation.
Thesis (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Overseas wo9rkers -- Families